Orthographic and Phonological Preview Benefits: Parafoveal Processing in Skilled and Less-Skilled Deaf Readers. Issue 11 (November 2013) - Bélanger, Nathalie N.; Mayberry, Rachel I.; Rayner, Keith
Many deaf individuals do not develop the high-level reading skills that will allow them to fully take part into society. To attempt to explain this widespread difficulty in the deaf population, much research has honed in on the use of phonological codes during reading. The hypothesis that the use of phonological codes is associated with good reading skills in deaf readers, though not well supported, still lingers in the literature. We investigated skilled and less-skilled adult deaf readers' processing of orthographic and phonological codes in parafoveal vision during reading by monitoring their eye movements and using the boundary paradigm. Orthographic preview benefits were found in early measures of reading for skilled hearing, skilled deaf, and less-skilled deaf readers, but only skilled hearing readers processed phonological codes in parafoveal vision. Crucially, skilled and less-skilled deaf readers showed a very similar pattern of preview benefits during reading. These results support the notion that reading difficulties in deaf adults are not linked to their failure to activate phonological codes during reading.